Intraoperative Cardiopulmonary Arrest in Children Undergoing Spinal Deformity Correction: Causes and Associated Factors. Issue 22 (November 2015) - Menga, Emmanuel N.; Hirschfeld, Cole; Jain, Amit; Tran, Dong-Phuong; Caine, Heather D.; Njoku, Dolores B.; Karol, Lori A.; Sponseller, Paul D.
Abstract : Study Design: Retrospective review. Objective: To report the incidence of and risk factors for intraoperative cardiopulmonary arrest (ICA) in children undergoing spinal deformity surgery. Summary of Background Data: Spinal deformities in children are associated with comorbidities that can pose substantial risks during surgery. Methods: We reviewed records of patients who underwent surgery at two pediatric tertiary-care hospitals from 2004 through 2014. Fisher exact test and the Student t test were used to compare ICA and non-ICA groups by patient diagnosis, estimated blood loss, number of vertebral levels fused, and proportion of blood volume lost (significance, P  < 0.05). We classified proximate causes of ICA based on hemoglobin, metabolic panel/electrolyte imbalance, electrocardiogram/echocardiography, and vital signs. Results: ICA occurred in 11 of 2524 (0.4%) patients. Patients with neuromuscular disorders had a 3-fold higher risk of ICA compared with those without neuromuscular disorders. At the time of ICA, hemoglobin levels were 5 g/dL or less in four patients, potassium was higher than 5.5 mEq/L in six patients, and ionized calcium was less than or equal to 1 mmol/L in two patients. There were significant differences between the ICA and non-ICA groups in mean number of vertebral levels fused (15 vs. 12), patient weight (34 vs. 49 kg), estimated blood loss (2623 vs . 959 mL), and proportion of blood volume lost (1.03 vs . 0.33) (all P  < 0.01). Suspected causes of ICA were cardiovascular causes (eight patients) and anaphylaxis, primary rhythm disturbance, and respiratory/airway cause (one patient each). The incidence of ICA for patients with idiopathic scoliosis was 0.13%. Ten of the 11 patients were successfully resuscitated, and one patient died. Conclusion: ICA occurs in approximately 0.4% of children undergoing spinal fusion surgery. Patients with neuromuscular disorders are at greater risk of ICA than those without these disorders. Level of Evidence: 3